Assessment of Facilities and Infrastructure for Physical Education at SMP Negeri 5 Sigi - Rivalwan; Mochammad Ridha Saputra M. Gazali; sardiman; Andi Saparia; Moh. Tris Maulana Daipaha; Muh. Saldi (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Efficiency learning eye lesson education physical , sports , and health very helped with availability means And infrastructure education physical . However , the situation on the ground show that Lots schools , especially those in rural areas , are still face constraint in provide facility the purpose . from study This is For know condition means And infrastructure education physical education at SMP Negeri 5 Sigi. Objectives. Goal study This is For know availability Means And Infrastructure Education Physical Sports and Health at SMP Negeri 5 Sigi. Materials and Methods. Types study This is Survey with method study Descriptive Quantitative , population in study This is SMP Negeri 5 Sigi. Results. Ratio means And infrastructure education physical education at SMP Negeri 5 Sigi varies . For example , the volleyball equipment at SMP Negeri 5 Sigi amount to two ball fruit , while The ideal number of Minister of National Education Regulations is at least six fruit ball with percentage of 33.33% is classified as lack of equipment football at SMP Negeri 5 Sigi there are five balls , meanwhile The ideal number of Minister of National Education Regulations is at least six fruit ball with percentage of 83.33% is classified as very good ; and basketball equipment at SMP Negeri 5 Sigi amount to two fruit ball, Equipment Athletics at SMP Negeri 5 Sigi consists of of 5 pieces , while ideal number of Permendiknas ( javelin , discus , shot put , baton) relay , tub jump ) with percentage 100% is classified as very good . Equipment gymnastics at SMP Negeri 5 Sigi consists of of 2 pieces , while ideal number of Permendiknas ( mattresses , crates jump rope​ jump , hoop , plastic ball , stick , crossbar single , bracelets ) minimum 8 pieces . Conclusion . Meanwhile results evaluation to condition means And infrastructure education physical And sport And health at SMP Negeri 5 Sigi very Good For branch sport athletics And football , but Still not enough For branch sports such as basketball, volleyball , and exercise .